1969
DOI: 10.1111/j.1432-1033.1969.tb00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver 3': 5'-Nucleotide Phosphodiesterase and its Activity in Rat Livers Perfused with Insulin

Abstract: Most (80–90%) of the cyclic 3′:5′‐nucleotide phosphodiesterase activity in 0.25 M sucrose homogenates of rat liver was found in the 100,000 ×g× 30 min supernatant. The non‐particulate nature of the liver phosphodiesterase activity was also confirmed with beef and human liver. The phosphodiesterase activity of rat liver supernatant showed a pH maximum in the region of 7.0–7.5 in Tris‐Cl or cacodylate buffer, with a Km of 62 μM in Tris‐Cl buffer. A dependency on added Mg++ was indicated for maximum phosphodieste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1969
1969
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…I n comparison with the total homogenate, a six-fold increase in specific enzyme activity was observed. I n spite of the extensive washing, a residual phosphodiesterase activity remained with this particle preparation which corresponded with specific activities of particulate fractions of rat liver as shown in an earlier report from this laboratory [14]. I n order to prevent breakdown of labeled Ado-3':5'-P in the reaction, theophylline, or the better soluble aminophylline were added to the incubation system at concentrations of 10 and 20 mM, respectively.…”
Section: Studies On the Assay Systemsupporting
confidence: 60%
See 1 more Smart Citation
“…I n comparison with the total homogenate, a six-fold increase in specific enzyme activity was observed. I n spite of the extensive washing, a residual phosphodiesterase activity remained with this particle preparation which corresponded with specific activities of particulate fractions of rat liver as shown in an earlier report from this laboratory [14]. I n order to prevent breakdown of labeled Ado-3':5'-P in the reaction, theophylline, or the better soluble aminophylline were added to the incubation system at concentrations of 10 and 20 mM, respectively.…”
Section: Studies On the Assay Systemsupporting
confidence: 60%
“…The particle preparation employed in the present work was therefore chosen to comprise most of the particulate material of the liver after washing away the soluble protein which contains most of the phosphodiesterase activity [14]. Preliminary studies of different homogenization techniques and different buffers showed the highest yield in adenyl cyclase activity after high speed mechanical homogenization in 0.2 M Tris-C1 at pH 7.4.…”
Section: Studies On the Assay Systemmentioning
confidence: 99%
“…The increase in cAMP1 is prevented by the acidification induced by acid-loading or amiloride treatment, suggesting that pHi modulates the activity of enzymes involved in cAMP formation [33,34]. Reynolds & Haugaard [35] reported that extractable phosphorylase activity in rat liver slices is significantly increased when external pH is 7.8.…”
Section: Effect Of Heat On Phosphodiesterasementioning
confidence: 99%
“…The present study indicates that Bu,Ado-3': 5'-P addition to the perfusion medium results in an increased endogenous urea, glucose and ketone body production in the isolated, perfused liver from fasted rats. The choice of Bu2Ado-3':5'-P instead of Ado-3' :5'-P as effector was based on the thinking that the derivative penetrates cell membranes more readily [24] and that it is more resistant to action of phosphodiesterase than Ado-3' :5'-P [24,25,. Levine [45] found that Bu,Ado-3' : 5'-P induces a three-fold greater glycogenolytic effect than the parent Ado-3': 5'-P compound in isolated, perfused liver.…”
Section: Effects Of Insulin and Buado-3' :5'-p On Endogenous Liver Mmentioning
confidence: 99%
“…An increase in phosphodiesterase activity in liver and muscle in vivo was observed by Schultz, Senft and Munske [65] following insulin administration to alloxan-diabetic rats. However, a lack of effect of insulin in vitro or in vivo on the activity of phosphodiesterase has been observed for the rat liver [25,66] and adipose tissue enzyme [48,66,67]. Although after incubation of the tissue with hormone a decrease in cyclase activity has been observed by prior incubation [68], a direct effect of insulin on this enzyme in adipose tissue homogenate is lacking [68,69].…”
Section: Effects Of Insulin and Buado-3' :5'-p On Endogenous Liver Mmentioning
confidence: 99%